A novel water-soluble naphthalimide-based turn-on fluorescent probe for mercury ion detection in living cells and zebrafish. (23rd May 2022) - Su, Meijun; Liu, Caiyun; Liang, Yuying; Zhang, Yan; Rong, Xiaodi; Wang, Xin; Li, Xiwei; Wang, Kun; Zhu, Hanchuang; Yu, Miaohui; Sheng, Wenlong; Zhu, Baocun
Abstract : A highly selective and sensitive water-soluble naphthalimide-based turn-on fluorescent probe was synthesized to detect Hg 2+ in living cells and zebrafish. Abstract : Mercury (Hg), as the only heavy metal that can complete the cycle in the biosphere, can further accumulate in the human body through the food chain, causing irreversible damage to the human liver, endocrine, bone, etc. Therefore, it is necessary to detect and remove mercury ions (Hg 2+ ). In this study, a new water-soluble naphthalimide-based turn-on fluorescent probe NIML for Hg 2+ was designed and synthesized by modifying with morpholine. The detection and removal of Hg 2+ could be realized by the binding of NIML with Hg 2+ to form a specific "imide–Hg–imide" structure. The binding of NIML and Hg 2+ resulted in aggregation, which can be observed by the Tyndall effect (TE). Fluorescence emission enhancement occurred when the probe combined with Hg 2+ ; this turn-on probe can effectively avoid the false positive signal caused by environmental factors and make the monitoring results more reliable. In addition, probe NIML has good water solubility and can be directly used to detect actual water samples without worrying about the aggregation of probe molecules in the aqueous solution. A toxicity test showed that probe NIML was less toxic and could be used for imaging living cells and zebrafish. Importantly, this study not only provides a new methodology for the design of simple water-soluble turn-on fluorescent dyes but also improves the shortcoming of insoluble naphthalimide dyes through structural optimization.